Produção do conhecimento acerca do processo de cuidar em saúde e enfermagem: uma metassíntese - Videres, Arieli Rodrigues Nóbrega (2019)
Objective: To analyze the knowledge production about the Health and Nursing care process. Methods: Systematic literature review and metasynthesis developed between March 2018 and November 2019, whose data source was the scientific production of Professor Lenilde Duarte de Sá, as informed in her Curriculum Lattes, at Lattes Plataform. Of the 74 articles that met the inclusion criteria, such as qualitative, complete studies, in Portuguese, English and/or Spanish, presenting in the title the descriptors care and/or Nursing care, and the keywords healthcare practices and/or healthcare management, conducted between 1995 and 2018, nine composed the empirical corpus after the performance of the Relevance Tests and the assessment of the methodological quality through the Critical Appraisal Checklist for Interpretive & Critical Research. The corpus was analyzed using the Thematic-Categorical Content Analysis. Results: The knowledge produced about the Health and Nursing care process points to the distance between the qualification process and healthcare practices; the weakening of the modes of production due to capitalism and the hegemony of the biomedical model of health focused on curing diseases; the challenges of healthcare management regarding the verticalization of health services and the possibilities and weaknesses of Primary Care that may result in evaluating healthcare practices. Final Thoughts: The social actors involved in care must expand and give new meanings to healthcare management considering the Primary Care model as the organizer and coordinator of the healthcare network in Health and Nursing. The use of metasynthesis in the analysis of health constructs, based on the scientific production of researchers in the field, is a groundbreaking and biased practice in both national and international literature. Implications for Nursing: The study contributes to the discussion of new propositions in Nursing qualification, management and care and in other fields of knowledge focused on integrality, ethics of alterity, and care humanization